APPLYING DIGITAL STORYTELLING TO IMPROVE INDONESIAN HIGH SCHOOL STUDENTS’ VISUAL MEMORY AND WRITING SKILL - Imam Sudarmaji; Agus Mulyana; Karsiyah Karsiyah (University of Kuningan, 2020)
This study investigated the use of digital storytelling in improving students’ visual memory and writing skill of tenth grade students in one of senior high school in Tangerang, Indonesia. A total of 72 students are taken as the sample in the current study. The randomized pretest - posttest control group design was used in the study. Using quasi experimental research-non-equivalent control group design, the students in the experimental groups completed the process through digital storytelling. The students’ test and questionnaires were used to collect the data. In order to test whether there was an improvement within groups and to see if there were differences between groups, the hypotheses were tested using the t-test and obtaining gain scores. The result showed that the visual memory and writing skill of students undergoing digital storytelling technique and of those undergoing conventional teaching but no significant differences were found between the two conditions. They had same proficiency, focused and same concentration during the learning process, and the students had many opinions in experimental class. Based on the percentages, students’ post-test showed that students’ visual memory was more dominant than students’ writing skill after applying digital storytelling. Moreover, this research also found that students’ learning motivation was very good and created a good of class atmosphere in experimental class during the learning process by using digital storytelling.